Hydroxychloroquine in obstetric antiphospholipid syndrome: rationale and results of an observational study of refractory cases. (12th December 2022) - Khizroeva, Jamilya; Bitsadze, Victoria; Tincani, Angela; Makatsariya, Alexander; Arslanbekova, Madina; Babaeva, Nigar; Tsibizova, Valentina; Shkoda, Andrei; Makatsariya, Natalya; Tretyakova, Maria; Solopova, Antonina; Gadaeva, Zumrad; et al.
Abstract: Background: The current recommended therapy of obstetric antiphospholipid syndrome (APS) is a long-term anticoagulant therapy that affects the final event, namely, when the thrombosis has already occurred. Unfortunately, this schedule is not always effective and fails despite the correct risk stratification and an adequate adjusted dose. Materials and methods: From 2013 to 2020 we observed 217 women with antiphospholipid antibodies and obstetric morbidities who were treated with conventional treatment protocol (aspirin low doses ± LMWH). Among them 150 (69.1%) successfully completed pregnancy with delivery and live birth on the background of LMWH and aspirin therapy and in 67 (30.9%) women despite a traditional therapy regimen, obstetric complications were noted. Later, 56 of these 67 women became pregnant again and were offered traditional therapy plus hydroxychloroquine. Fifteen women refused HCQ treatment due to possible potential side effects. The final cohort consisted of 41 women with positive antiphospholipid antibodies and obstetric and thrombotic complications who received LMWH, aspirin low doses and HCQ at a dose of 200–400mg per day from the beginning of pregnancy. Results: Forty-one aPL women treated with HCQ after failed previous anticoagulant therapy had live births in 32 cases (78%). Adding of HCQ to the combination of LMWH and LDA showed good overall obstetric results and increased the number of live births in another 32 women. So, a total of 182 (83.8%) of initial 217 aPL-women ended their pregnancies with live birth after adding the HCQ to the traditional therapy with LMWH and low doses of aspirin. Conclusion: In 20–30% of cases the live birth despite anticoagulation cannot be achieved. Perhaps APS is not just anticoagulation. The study of pathophysiological mechanisms suggests that some patients will benefit from other therapy (in addition to anticoagulant). Therapy that affects the early effects of aPL on target cells (monocytes, endothelial cells, etc.) or before binding to receptors–this therapy will be preferable and potentially less harmful than the officially accepted one to date. From this point of view, HCQ looks promising and can be used as an alternative candidate for women with refractory obstetric antiphospholipid syndrome. Adding HCQ should be considered in some selected patients with failed pregnancy after treatment with anticoagulants.